Grain Size Associations of Branched Tetraether Lipids in Soils and Riverbank Sediments: Influence of Hydrodynamic Sorting Processes - Peterse, Francien; Eglinton, Timothy I. (Frontiers in Earth Science, 2017)
We analyzed the abundance and distribution of branched glycerol dialkyl glycerol tetraethers (brGDGTs) in grain size fractions of 7 globally distributed river flank sediments and catchment soils in order to determine if and how the initial soil-brGDGT signature is influenced by hydrodynamic sorting upon entering a river and during subsequent transport from land to sea. BrGDGTs are hypothesized to form associations with high-surface-area fine-grained minerals in soils. Such associations, if maintained during transport, may impart resistance to degradation and promote downstream transport, reducing potential interferences by aquatic brGDGTs. We find that brGDGTs are indeed primarily associated with organic carbon (OC) bound to the clay-silt fraction (<63μm) in both soils and river sediments, and that these associations appear to be maintained during river transport. However, the relative distribution of individual brGDGTs among size fractions is relatively uniform, suggesting that brGDGTs are well mixed in river sediments and that OC-mineral associations are continuously renewed. Consequently, the brGDGT signature finally stored in continental margin sediments appears insensitive to differential particle transport processes. Nevertheless, the lower (upstream) temperature signal generally reflected by brGDGTs in river sediments may also be explained by a contribution of in situ produced brGDGTs leading to an underestimation of reconstructed air temperatures.